PENGARUH PROGRAM PEMBERDAYAAN INDUSTRI RUMAH TANGGA ANEKA KERIPIK TERHADAP KEBERDAYAAN PELAKU USAHA MENUJU KEBERLANJUTAN USAHA (STUDI KASUS KELOMPOK USAHA SUKOPURI DI KECAMATAN PRAMBANAN KABUPATEN SLEMAN) - Nugraheni, Tyas Ayu; Soeharto, Soeharto; Widowati, Indah (Jurnal Dinamika Sosial Ekonomi, 2015)
The purpose of this study were: (1) Analyze the effect of mentoring and training of household industry against various chips empowerement group businesses sukopuri in pambanan district. (2) Analyze the influence of technology, production, marketing and parterships for the sustainable livelihood of various chips industry business group SUKOPURI in Prambanan District. The research method used was a case study. The population was Business Group SUKOPURI in Prambanan District. The method used to letermine the respondentsin this study is the method observation, interviews and questionnaires. The analytical method used is multiple linear regression analysis. The results of the analysis of mentoring and training affect the empowerment of businesses various chips and factors technological, marketing and partnerships effect on the business sustainability of various chips.Keywords: Empowerment, Household Industry. The Sustainable Livelihood